2021
DOI: 10.1002/jcsm.12738
|View full text |Cite
|
Sign up to set email alerts
|

Muscle strength is associated with COVID‐19 hospitalization in adults 50 years of age or older

Abstract: Background Weak muscle strength has been associated with a wide range of adverse health outcomes. Yet, whether individuals with weaker muscle strength are more at risk for hospitalization due to severe COVID‐19 is still unclear. The objective of this study was to investigate the independent association between muscle strength and COVID‐19 hospitalization. Methods Data from adults 50 years of age or older were analysed using logistic models adjusted for several chronic c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 41 publications
2
40
0
2
Order By: Relevance
“…A recent review of prospective cohort studies found epidemiologic evidence that musclestrengthening activities might contribute to reducing the risk of major chronic diseases [28], and even small-to-moderate increases might bring measurable public health benefits [29]. Muscle strength has been shown to be associated with a lower risk to be hospitalized because of COVID-19 in older adults even after adjusting for established risk factors for severe COVID-19 [30]. Prevalence of muscle-strengthening activities is, generally speaking, lower than that of endurance activities [31].…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of prospective cohort studies found epidemiologic evidence that musclestrengthening activities might contribute to reducing the risk of major chronic diseases [28], and even small-to-moderate increases might bring measurable public health benefits [29]. Muscle strength has been shown to be associated with a lower risk to be hospitalized because of COVID-19 in older adults even after adjusting for established risk factors for severe COVID-19 [30]. Prevalence of muscle-strengthening activities is, generally speaking, lower than that of endurance activities [31].…”
Section: Discussionmentioning
confidence: 99%
“…In response to the COVID-19 pandemic, many countries have implemented policies for social distancing and varying degrees of quarantine or isolation at home ( 13 ). Such strategies have had unintended negative effects on the functional fitness of older adults ( 33 , 34 ) due to decreased physical activity and increased sedentary behavior ( 14 , 15 ). Therefore, based on the results of this study, we propose that live-streaming home-based exercise programs may be an effective alternative method for increasing the functional fitness of community-dwelling older adults during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Gil et al assessed 196 hospitalized patients for vastus lateralis cross-sectional area using ultrasonography and concluded that low muscle mass contributes to higher skeleton muscle loss among COVID-19 patients due to increased demands of tissues such as liver and immune cells [90]. Those patients with weak muscle strength are more vulnerable to stress factors, which could be the case of COVID-19 [91,92]. Other studies have found that with COVID-19 treatment, 43% of study participants lost ≥5% of their body weight, and 25% of participants lost ≥10% of their body weight.…”
Section: Sars-cov-2 (Covid-19) Induced Cytokine Storm In Muscle Wasti...mentioning
confidence: 99%